Optimizing cooperation strategies for new energy vehicle manufacturers and technology suppliers: A game theory approach - Wang, Y. L. (Advances in production engineering and management, 2025)
New energy vehicle manufacturers usually choose to cooperate with technology suppliers to improve their products’ market competitiveness. For this purpose, this paper constructs a single and dual sales-channel supply chain system comprising a technology supplier and a new energy vehicle manufacturer. Within this framework, the technology supplier acts as the leader in a Stackelberg game, while the new energy vehicle manufacturer acts as the follower. Based on intelligent driving cooperation cases between Huawei and Chang’an, BYD, and Seres, three cooperation modes—“technology introduction + own sales channel (Model A)”, “cooperative R&D + own sales channel (Model B)”, and “technology introduction + channel support (Model C)”—are examined to analyze cooperation mode selection strategies for the new energy vehicle manufacturer and the technology supplier. The study found that when the profit ratio of technology supplier to the new energy vehicle manufacturer (referred to as the revenue sharing coefficient) meets certain conditions, the optimal cooperation mode of the new energy vehicle manufacturer and technology supplier is Model C. Additionally, the profit obtained by the technology supplier under Model A is always the smallest, while the profit size between the other two models depends on the revenue sharing coefficient. Moreover, five situations describe the profit outcomes of the new energy vehicle manufacturer across the three cooperation modes, which are affected by the revenue sharing coefficient and the proportion of the technology supplier’s R&D investment cost. This study addresses a gap in research on cooperation modes within the new energy vehicle sector, and the conclusions obtained can provide valuable theoretical insights for new energy vehicle manufacturers and technology suppliers when selecting cooperation strategies.
Keywords: cooperation modes; dobavitelji tehnologije; electric vehicle industry; game theory; igra Stackelberg; industrija električnih vozil; new energy vehicle manufacturers; R&D investment; Stackelberg game; supply chain management; technology suppliers